A Face Recognition Method in the Internet of Things for Security Applications in Smart Homes and Cities - Othman, Nashwan Adnan; Aydin, Ilhan (Ieee, 2018)
In recent years, the security constitutes the most important section of the human life. At this time, the cost is the greatest factor. This system is very useful for reducing the cost of monitoring the movement from outside. In this paper, a real-time recognition system is proposed that will equip for handling images very quickly. The main objective of this paper is to protect home, office by recognizing people. For this purpose, the PIR sensor is used to detect movement in the specific area. Afterwards, the Raspberry Pi will capture the images. Then, the face will be detected and recognized in the captured image. Finally, the images and notifications will be sent to a smartphone based IoT by using Telegram application. The proposed systems are real-time, fast and has low computational cost. The experimental results show that the proposed face recognition system can be used in a real time system.
6th International Istanbul Smart Grids and Cities Congress and Fair (ICSG) -- APR 25-26, 2018 -- Istanbul, TURKEY
Keywords: Internet of things; Computer Vision; Raspberry Pi 3; Face recognition; Telegram